A look at ethical issues in action research in education - Banegas, Darío Luis; Villacañas de Castro, Luis S. (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
This reflective contribution covers a wide range of ethical issues which are bound to arise when teacher-researchers engage in technical, practical or critical models of action research. Once these three models are briefly explained, the paper proceeds to justify why ethical dilemmas are an intrinsic part of action research, precisely on account of its collaborative nature and of the diverse motivations, perspectives, and institutional roles held by its participants. As a result, questions around power and control are also likely to arise. Hence, we stress the need for action researchers to anticipate these ethical issues and be prepared to handle them through sincere and respectful dialogue among all participants.